Quantitative evaluation and prediction for preservation quality of cold shocked cucumber based on entropy. (June 2016) - Chen, Aiqiang; Yang, Zhao; Zhang, Na; Zhao, Songong; Chen, Mingfeng
Abstract: To evaluate and predict preservation quality of cold shocked cucumber and study the effects of cold shock parameters on the preservation quality, several entropy-based models were proposed. Cucumbers were cold shocked at different temperatures (0, 3, 6 °C) for different durations (20, 40, 60 min), and their preservation quality was evaluated by the proposed models. Results show that, the evaluation model can objectively evaluate preservation quality of cold shocked cucumber, and cold shocked at 3 °C for 40 min gets optimal preservation effect. Cold shock treatments at 0 °C and 3 °C improve preservation quality of cucumber effectively, while that at 6 °C fails. Therefore, entropy change caused by cold shock treatment should be higher than a certain critical value to improve preservation quality of cucumber effectively, and the duration is crucial for preservation quality when meeting this condition. The composite entropy change ( S *) shows effect of both temperature and duration and characterizes cold shock intensity, and proposed prediction model of cold shock preservation quality can predict preservation quality of cucumber cold shocked at different temperatures and durations well. Industrial relevance: Fresh fruits and vegetables contain rich essential substances to our bodies and play an active role in improving people's health. Since it has obvious seasonal regional characteristics on the fruits and vegetables production, pretreatment is very important for prolonging their storage periods. Cold shock treatment for many fruits and vegetables indicate that this method can effectively improve their preservation quality and have broad application space. This study lies in providing a series of methods based on entropy to characterize the cold shock intensity to fruits and vegetables, carrying out objective quantitative evaluation and prediction for preservation quality of the cold shock treatment, and based on which, the influence mechanism of cold shock intensity (temperature and duration) on preservation quality of fruits and vegetables was analyzed. The results will contribute to better design and optimization of the cold shock process for postharvest fruits storage. Highlights: Cucumbers were cold shocked with different temperature and duration. Preservation quality of cucumbers was evaluated by entropy weight method. Effects of cold shock parameters on preservation quality were illustrated. Cold shocked intensity was characterized based on entropy. A model was put forward based on entropy to predict preservation quality.